THE A CORRELATION STUDY ABOUT SIZE OF SMARTPHONE AND PARESTHESIA IN PALMAR CAUSED BY CONSTRICTION AT CARPAL TUNNEL IN STUDENTS OF MEDICAL FACULTY UDAYANA UNIVERSITY - Fridayani, Ni Kadek Yuni; Andayani, Ni Luh Nopi; Tianing, Ni Wayan (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT   Using smartphone in different size can give different effectwhilehold and swipe smartphone so, this study was to analyze the relationship between the size of smartphone and paresthesia in palmar caused by constriction at carpal tunnel. Cross sectional analytic study with subjects were 109 students of Medical Faculty Udayana University. The sample of this study is the students who scored SAS (Smartphone Addiction Scale) ? 84, inclusion and exclusion. The participants asked to use a smartphone for 30 minutes, one-handed while maintaining comfortable sitting postures on a chair. The result showed no significant correlation between the size of smartphone and paresthesia in palmar caused by constriction at carpal tunnel and also was found that smartphone large more cause paresthesia in palmar (46,5%) than small category (39,5%) and medium (14,0%). Subjects were more fatigue in thumb and finger after using smartphone than paresthesia. So, the use of smartphones with large category can caused paresthesia and continued with musculoskeletal problem especially in thumb.   Keywords : size of smartphone, paresthesia, constriction at carpal tunnel